DAMPAK PRAKTIK BANK TITHIL TERHADAP KESEJAHTERAAN EKONOMI MASYARAKAT DALAM PERSPEKTIF EKONOMI ISLAM - Dewi Kumalasari; Suyitno (Tamaddun, 2024)
This study aims to analyze the impact of bank tithil practices on the economic welfare of society and examine them from the perspective of Islamic economics. Using a descriptive qualitative approach through interviews and observations in Banjar Village, the study found that bank tithil practices provide easy access to capital but create dependency, high interest burdens, and a decline in welfare. From an Islamic perspective, this practice contains elements of riba and contradicts the principles of justice, mutual assistance, and overall welfare (falah).